Analisis Perbandingan Model Altman, Grover, Zmijewski Dan Springate Sebagai Prediksi Financial Distress - Enggar Prasetianingtias; Dewi Kusumowati (University of Merdeka Malang, 2019)
This study aims to compate the accuracy of Altman, Grover, Zmijewski and Springate models to predict financial distress. Comparison has done by analyzing the level of accuracy of each model. The variables in this study are the financial ratios of Altman, Grover, Zmijewski, and Springate towards accuracy in predicting Financial Distress.The data has been taken from annual financial reports that published on the Indonesian Stock Exchange website. The sample used is an agriculture company listed on the IDX during 2016-2017. The sampling technique was purposive sampling with a total sample of 34 companies. The criteria in purposive sampling are companies that publish annual financial statements in the period 2016-2017 and stock price data are available on the trading date ending in the year.The results show that the Grover G-Score model is a prediction model with a high accuracy of 85.29% by comparing it with actual conditions. The percentage comparison of Negative Net Income and dividend payment in the Grover model has a percentage of 85%. The Springate model has an accuracy rate of 83.82%, Altman with an accuracy rate of 68.65% and the last is Zmijewski with an accuracy of 25%. DOI: https://doi.org/10.26905/ap.v5i1.3072